Experimental analysis of encapsulated CaO/Ca(OH)2 granules as thermochemical storage in a novel moving bed reactor. (25th March 2020) - Cosquillo Mejia, Aldo; Afflerbach, Sandra; Linder, Marc; Schmidt, Matthias
Highlights: Development and demonstration of a novel moving bed reactor concept. Encapsulation of Ca(OH)2 with ceramic shell and Al2 O3 nanostructured particles. Experimental investigation of encapsulated materials in a lab scale reactor. Enhancement of stability of Ca(OH)2 granules along multiple thermochemical cycles. Encapsulated granules investigated under application-oriented operating conditions. Abstract: The advantages of Ca(OH)2 such as low cost and high energy density make it a promising material for thermal energy storage. However, the development of cost efficient large scale storage systems remains challenging. One reason is that the low thermal conductivity and cohesiveness of the powder bulk material impede the reliable operation of moving bed reactors. One approach to address these drawbacks is the macro encapsulation of pre-granulated storage material. In this work, a newly moving bed reactor was developed and the performance of two encapsulated storage materials was investigated in lab scale and under application relevant boundary conditions. The two tested material samples were ceramic encapsulated CaO granules (sample 5D1F) and Ca(OH)2 granules coated with Al2 O3 nanostructured particles (sample Al2 O3 ). The reaction performance, cycling stability and ability to flow were experimentally examined and the operation of the moving bed reactor was successfully demonstrated. It was found that both encapsulated materials retained their shape after sixfold cycling. After the experiment series, the sample 5D1F flowed freely out of the reactor while the sample Al2 O3 clogged the reactor tubes due to the volume expansion during hydration. Further, the experiments revealed that the reaction performance of the sample 5D1F is reduced, while the performance of the sample Al2 O3 is comparable to unmodified Ca(OH)2 granules. Overall, this study shows that encapsulated granules are stable under operation in larger reactors and the granules further facilitate the reactor design and operation. Additionally, the volumetric energy density of compacted granules is higher compared to the loose powder bulk. In particular, the encapsulation with Al2 O3 nanostructured particles showed promising performance for the cost efficient development of a scalable thermochemical energy storage system and therefore needs to be further investigated.